Uso de filmes eletrofiados de PBAT e PCL para liberação de fármacos - Hardt, Janice Caroline (2019)
In this work, two polymers were used to produce a polymeric blend, such as poly (εcaprolactone) (PCL) and poly (butylene-adipate-co-terephthalate) (PBAT) - Ecoflex®, with the aim of promoting a sustained release of the drug ibuprofen and silver sulfadiazine. The films were obtained using the electrospinning technique. Because PBAT is fully biodegradable, it has high resistance and biodegradability, and is allied to PCL that is biocompatible, bioreabsorbable and has high porosity. In this polymer blend, two drugs were incorporated in different films, varying the concentrations of the drugs in PBAT and PCL films, for the films with ibuprofen, 20% and 30% w/w, and for the films with silver sulfadiazine, 10% and 20% w/w. It was obtained fibers with very irregular beads and with these fibers the films were produced and characterized by Differential Scanning Calorimetry (DSC), Thermogravimetry (TGA), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Fourier transform infrared (FTIR), by mechanical analysis and wettability assessment. Through these analyzes it was possible to identify the incorporation of both ibuprofen and silver sulfadiazine, as well as their probable interactions with the polymers, mainly demonstrating the change in crystallinity of this material. Drug release studies of the two films produced with ibuprofen was performed, showing satisfactory result for possible use as skin dressings. The release in the film with 20% w/w ibuprofen occurred up to 840 minutes, releasing 64% of the drug incorporated into the film and releasing the film with 30% w/w ibuprofen also for a period of 840 minutes, releasing about 58% of the drug initially added. The release procedures were also performed for films with silver sulfadiazine, which presented significantly lower release results due to their low solubility and likely presence inside the fibers/beads. For the film containing 10% w/w of silver sulfadiazine, the liberation was achieved in up to 3% of the total incorporated for a period of approximately 4440 minutes, and in the film with 20% w/w of silver sulfadiazine, 2% of the initial amount incorporated into the film was released for a period of 4440 minutes. Through the evaluation of the adjusted determination coefficient (R2ajus), the Akaike Information Criterion (AIC) and the Model Selection Criteria (MSC), which prove the best mathematical adjustment to explain the release kinetics of the drugs, it was observed that for the release in the two concentrations of the drug ibuprofen, the mathematical model that better fits was Gompertz and for the two concentrations of silver sulfadiazine incorporated into the films, the mathematical model that had the best fit was that of Peppas-Sahlin.